Malnutrition: a mascaraed and underused prognostic marker in coronary patients. (2nd July 2022) - Martinho, A; Almeida, J; Goncalves, F; Monteiro, S; Franco, F; Goncalves, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Malnutrition had been associated with worse prognosis in heart failure (HF) patients, especially in elder. However, this association wasn't demonstrated in coronary patients, after a ST-segment elevation myocardial infarction (STEMI). We want to evaluate the prognosis value of malnutrition, in elder patients, after a STEMI. Methods: We conducted a retrospective, observational study of 200 elderly patients ( 3 65 years) consecutively admitted with STEMI between 2016 and 2017. At discharge, we applied a validated formula who evaluate nutritional status: "Prognostic Nutritional Index" (PNI), [10 x serum albumin at discharge (g/dL) + 0.005 x total lymphocytes at discharge], whose lowest values were associated with malnutrition. At 1 year follow-up, we evaluated the relation between PNI and major adverse cardiac events (MACE): myocardial infarction (MI), HF hospitalization, cardiovascular (CV) and all-cause death. Results: Mean age was 74±8 years, 71% (n=149) were male and with multiples risks factors (75% hypertense, 63% with dyslipidemia, 33% diabetes and 11% smokers). At discharge, patients had a mean Left Ventricular Ejection Fraction (LVEF) of 47±8% and a mean PNI of 37±5. Low PNI values (malnutrition) were significant associated with MACE at 1-year [OR 0.87 (95% CI 0.78 to 0.97, p=0.01)], after adjusting for age, sex and LVEF. When evaluated individually, low PNI was associated with more incidence of 1-year HF hospitalization [OR 0.88 (95% CI 0.78 to 0.99, p=0.03)] and all-cause death [OR 0.84 (95% CI 0.75 to 0.95, p=0.004)], after adjusting for age, sex and LVEF, but not with MI and CV death. Conclusion: Malnutrion associated with other comorbidities inherent to elderly people were associated with MACE, 1-year after STEMI, in this type of population. Thus, we want to draw attention to the importance of evaluating the nutritional status during hospitalization for STEMI, allowing to initiate measures that contribute to its improvement.